Nannecōḍuni Kumārasambhavamu - Appalanarasiṃhamūrti, Upādhyāyula (Sīrīs, 1979)
On the Kumārasambhavamu, poem about the marriage of Siva and Parvati and the birth of their son Kumara, Hindu deity, by Nannecōḍa, fl. 1100; brief study.